Síntese e caracterização das propriedades mesomórficas e óticas de cristais líquidos fotorresponsivos derivados do azobenzeno - Moreira, Thamires dos Santos (2015)
Liquid crystals (LCs) are functional soft materials of dynamic nature with shape and anisotropic properties. Control of the intrinsic self-assembly and self-organization properties in LCs may be accomplished by incorporating an optical switch within the mesogenic structure, such as a photoresponsive azo group. In this context, this dissertation shows the synthesis and characterization of the mesomorphic and optical properties of compounds derived from 1,4-disubstituted azobenzenes. The molecules are designed in order to contain an azobenzene rod-shaped rigid core. At one end, the molecules hold substituents with different sizes, polarity, and electronic properties (NO2, Cl or OR groups). At the other end of the molecules are connected, via an eter bond, to chains of 6 or 11 carbons possessing a terminal polar hydrophilic group, such as hydroxyl or imidazolium salt. In another series of molecules, the peripheral region is built on anhydrophobic portion. They contain an high dipole moment carbonyl group of aliphatic and aromatic ester with or without mesogenic extension. The chemical structures of final compounds were characterized by spectrometric methods (IR,1H and 13C NMR). The mesomorphic properties were investigated by Polarizing Optical Microscopy and Differential Scanning Calorimetry. Among the eighteen molecules synthesized, seven are LCs. Our studies reveal an interesting relation between the stereoeletronic nature of terminal groups and the observed LC phase. The hydroxyl group generated nematic phase, while compounds with ester carbonyl show a lamellar polymorphism with SmA and SmC phases, indicating the carbonyl increase the stability of liquid crystalline phases. The compounds containing terminal imidazolium salts show only SmA phase with an interesting characteristic of keeping the phase up to room temperature. Preliminar studies of the azo group photoisomerization indicate that the phase may be broken by expose to UV light. Thus, this molecular system may have potential technological applications in the photocontrol of liquid crystalline phase and enhanced functions in optoelectronic devices.